(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
When we make an array with only the real constants of a linear equation or a system of linearequations, we get a matrix. There are various types of matrices that are identified and defined based ontheir structure, which includes elements in various ways and in various positions. This research paperwill discuss a matrix that is distinct from other types of matrices described in books and papers. Thispaper discusses some of the matrix’s most important properties and characteristics.